Make it personal: Tips on customizing academic integrity talks for the audience - Packalen, Kelley A (Canadian Perspectives on Academic Integrity, 2023)
Speaking about academic integrity with students can be challenging. In this session I will demonstrate how I moved beyond the traditional policy overview lecture, to engage audiences in interactive, research-based discussions that were focused on 1) addressing the root causes of academic integrity adherence/violation unique to that group; 2) debunking myths around academic integrity; 3) providing customized explanations of why departing from academic integrity is detrimental; and 4) highlighting resources focused on treating the root causes (e.g. unintentional plagiarism, poor time management, mental health) of many violations. Examples from talks given to first year undergraduate students, students in a professional program in which academic integrity adherence was low, and to MSc/PhD students who had recently received access to similarity detection reports will be shared. Participants who attend this session will leave with 1) examples of how to bring academic research into non-research settings; 2) a set of questions that they can use to help them to customize their own presentations based on the audience to which they are presenting; 3) ideas of how to form a connection with their audience through the use of relevant examples; and 4) tips on how to engage with their audience through polls.